1\7 nhân 4=..... x:5\2=6...... mọi người giúp em nhanh với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{13}{20}+\dfrac{3}{5}+x=\dfrac{5}{6}\)
\(\Rightarrow\dfrac{5}{4}+x=\dfrac{5}{6}\)
\(\Rightarrow x=\dfrac{5}{6}-\dfrac{5}{4}\)
\(\Rightarrow x=\dfrac{-5}{12}\)
b) \(x+\dfrac{1}{3}=\dfrac{2}{5}-\dfrac{-1}{3}\)
\(\Rightarrow x+\dfrac{1}{3}=\dfrac{11}{15}\)
\(\Rightarrow x=\dfrac{11}{15}-\dfrac{1}{3}\)
\(\Rightarrow x=\dfrac{2}{5}\)
c)\(\dfrac{-5}{8}-x=\dfrac{-3}{20}-\dfrac{-1}{6}\)
\(\dfrac{-5}{8}-x=\dfrac{1}{60}\)
\(\Rightarrow x=\dfrac{-5}{8}-\dfrac{1}{60}\)
\(\Rightarrow x=\dfrac{-77}{120}\)
d) \(\dfrac{3}{5}-x=\dfrac{1}{4}+\dfrac{7}{10}\)
\(\Rightarrow\dfrac{3}{5}-x=\dfrac{19}{20}\)
\(\Rightarrow x=\dfrac{3}{5}-\dfrac{19}{20}\)
\(\Rightarrow x=\dfrac{-7}{20}\)
e) \(\dfrac{-3}{7}-x=\dfrac{4}{5}+\dfrac{-2}{3}\)
\(\Rightarrow\dfrac{-3}{7}-x=\dfrac{2}{15}\)
\(\Rightarrow x=\dfrac{-3}{7}-\dfrac{2}{15}\)
\(\Rightarrow x=\dfrac{-59}{105}\)
g) \(\dfrac{-5}{6}-x=\dfrac{7}{12}+\dfrac{-1}{3}\)
\(\Rightarrow\dfrac{-5}{6}-x=\dfrac{1}{4}\)
\(\Rightarrow x=\dfrac{-5}{6}-\dfrac{1}{4}\)
\(\Rightarrow x=\dfrac{-13}{12}\)
=> 72 - 20x - 36x - 84 = 30x - 240 - 6x + 84
=> (72 - 84 ) - (20x + 36x ) = (30x - 6x ) - 240 + 84
=> -12 - 56x = 24x - 156
=> -12 + 156 = 24x + 56x
=> 144 = 80x
=> x = 144 : 80
=> x = 9/5
a) x12 + 4 = x12 + 4x6 + 4 - 4x6 = (x6 + 2)2 - (2x3)2
= (x6 - 2x3 + 2)(x6 + 2x3 + 2)
b) 4x8 + 1 = 4x8 + 4x4 + 1 - 4x4 = (2x4 + 1)2 - (2x2)2
= (2x4 + 2x2 + 1)(2x4 - 2x2 + 1)
c) x7 + x5 - 1 = x7 - x + x5 + x2 - (x2 - x + 1) = x(x6 - 1) + x2(x3 + 1) - (x2 - x + 1)
= x(x3 - 1)(x3 + 1) + x2(x + 1)(x2 - x + 1) - (x2 - x + 1)
= (x4 - x)(x + 1)(x2 - x + 1) + (x3 + x2)(x2 - x + 1) - (x2 - x + 1)
= (x5 + x4 - x2 - x + x3 + x2 - 1)(x2 -x + 1)
= (x5 + x4 + x3 - x - 1)(x2 - x + 1)
d) x7 + x5 + 1 = x7 - x + x5 - x2 + (x2 + x + 1)
= x(x3 - 1)((x3 + 1) + x2(x3 - 1) + (x2 + x + 1)
= (x4 + x)(x - 1)(x2 + x + 1) + x2(x - 1)((x2 + x + 1) + (x2 + x + 1)
= (x2 + x + 1)(x5 - x4 + x2 - x + x3 - x2 + 1)
= (x2 + x + 1)(x5 - x4 + x3 - x + 1)
13 - 12 + 11 + 10 - 9 + 8 - 7 + 5 -4 + 3 + 2 - 1
=13
k nha
nan ni do
13 - 12 + 11 - 10 - 9 + 8 - 7 - 6 + 5 - 4 + 3 + 2 - 1
= ( 13 - 12 + 11 - 10 + 8 ) - ( 9 + 1 ) - ( 6 + 4) + ( 3 + 2 + 5 ) - 7
= 10 - 10 - 10 + 10 - 7
= ( 10 - 10 ) - ( 10 - 10 ) - 7
= 0 - 0 - 7
= - 7
a: 14/5-7/5=7/5
b: 7/8-1/3+5/4
=21/24-8/24+30/24
=43/24
c; =7/6+5/6+2/15+13/15
=2+1
=3
d: =4*5/3*11=20/33
e: =2/9*1/6*1/4=2/9*1/24=1/108
2:
a: \(=\dfrac{3}{9}\cdot\dfrac{4}{4}\cdot\dfrac{5}{5}\cdot\dfrac{6}{6}\cdot\dfrac{7}{7}=\dfrac{1}{3}\)
b: \(=\dfrac{1}{6}\left(\dfrac{22}{3}-\dfrac{2}{3}\right)=\dfrac{10}{3}\cdot\dfrac{1}{6}=\dfrac{10}{18}=\dfrac{5}{9}\)
c; \(=\dfrac{1}{3}\left(9-\dfrac{2}{5}-\dfrac{3}{5}\right)=\dfrac{8}{3}\)
`@` `\text {Ans}`
`\downarrow`
`1)`
\(2x+\dfrac{1}{2}=\dfrac{5}{3}\)
`\Rightarrow`\(2x=\dfrac{5}{3}-\dfrac{1}{2}\)
`\Rightarrow`\(2x=\dfrac{7}{6}\)
`\Rightarrow`\(x=\dfrac{7}{6}\div2\)
`\Rightarrow`\(x=\dfrac{7}{12}\)
Vậy, `x = 7/12`
`2)`
\(\dfrac{1}{7}+\dfrac{4}{5}x=\dfrac{5}{3}\)
`\Rightarrow`\(\dfrac{4}{5}x=\dfrac{5}{3}-\dfrac{1}{7}\)
`\Rightarrow`\(\dfrac{4}{5}x=\dfrac{32}{21}\)
`\Rightarrow`\(x=\dfrac{32}{21}\div\dfrac{4}{5}\)
`\Rightarrow`\(x=\dfrac{40}{21}\)
Vậy, `x = 40/21`
`3)`
\(\dfrac{3}{5}-\dfrac{3}{5}x=\dfrac{1}{7}\)
`\Rightarrow`\(\dfrac{3}{5}x=\dfrac{3}{5}-\dfrac{1}{7}\)
`\Rightarrow`\(\dfrac{3}{5}x=\dfrac{16}{35}\)
`\Rightarrow`\(x=\dfrac{16}{35}\div\dfrac{3}{5}\)
`\Rightarrow`\(x=\dfrac{16}{21}\)
Vậy, `x = 16/21`
`4)`
\(\dfrac{5}{6}-3x=\dfrac{3}{4}\)
`\Rightarrow`\(3x=\dfrac{5}{6}-\dfrac{3}{4}\)
`\Rightarrow`\(3x=\dfrac{1}{12}\)
`\Rightarrow`\(x=\dfrac{1}{12}\div3\)
`\Rightarrow`\(x=\dfrac{1}{36}\)
Vậy, `x = 1/36`
`5)`
\(\dfrac{5}{3}-\dfrac{1}{2}x=\dfrac{3}{7}\)
`\Rightarrow`\(\dfrac{1}{2}x=\dfrac{5}{3}-\dfrac{3}{7}\)
`\Rightarrow`\(\dfrac{1}{2}x=\dfrac{26}{21}\)
`\Rightarrow`\(x=\dfrac{26}{21}\div\dfrac{1}{2}\)
`\Rightarrow`\(x=\dfrac{52}{21}\)
Vậy, `x = 52/21`
`6)`
\(5x+\dfrac{1}{2}=\dfrac{2}{3}\)
`\Rightarrow`\(5x=\dfrac{2}{3}-\dfrac{1}{2}\)
`\Rightarrow`\(5x=\dfrac{1}{6}\)
`\Rightarrow`\(x=\dfrac{1}{6}\div5\)
`\Rightarrow`\(x=\dfrac{1}{30}\)
Vậy, `x = 1/30.`
\(\dfrac{1}{7}\times4\)
\(=\dfrac{4}{7}\)
\(x:\dfrac{5}{2}=6\)
\(x=6\times\dfrac{5}{2}\)
\(x=\dfrac{30}{2}=15\)
\(\dfrac{1}{7}\) x 4 = \(\dfrac{1}{7}\) x \(\dfrac{4}{1}\) = \(\dfrac{4}{7}\)
x : \(\dfrac{5}{2}\) = 6
x : \(\dfrac{5}{2}\) = \(\dfrac{6}{1}\)
x = \(\dfrac{6}{1}\dfrac{ }{ }\) x \(\dfrac{5}{2}\)
x = \(\dfrac{30}{2}\)
x = 15